L =
Find
JFF - I used L to celebrate launch of Android 5.0 Lollipop :P
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Assuming that the limit is as x → 0 + , then we first note that the limit is of the indeterminate form 0 0 .
So we look instead at
ln ( L ) = ln ( lim x → 0 + ( sin ( x ) ) ln ( x ) 1 ) = lim x → 0 + ( ln ( ( sin ( x ) ) ln ( x ) 1 ) = lim x → 0 + ln ( x ) ln ( sin ( x ) ) .
Now apply L'Hopital's rule to this last expression to find that
ln ( L ) = lim x → 0 + x 1 sin ( x ) cos ( x ) = lim x → 0 + x sin ( x ) cos ( x ) = 1 1 = 1 ,
where I made use of the fact that lim x → 0 x sin ( x ) = 1 .
So since ln ( L ) goes to 1 as x → 0 + , we conclude that L goes to e 1 = e = 2 . 7 1 8 2 8 . . . . . . Thus ⌊ L ⌋ = 2 .